2018
DOI: 10.1002/nau.23731
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin ameliorates cisplatin‐induced cystopathy via activating NRF2 pathway

Abstract: Taken together, the results of this paper showed that curcumin could ameliorate cisplatin-induced cystopathy and inhibit the apoptosis of bladder cell in cisplatin-treated rats. This may be attributed to curcumin's broad biological functions, particularly antioxidant effect, and to its ability to activate the NRF2 protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Cisplatin is an effective anticancer drug, but it has demonstrated toxicity to the bladder [15], inner ear [16], peripheral nerves [17], and reproductive system [15]. Melatonin is capable of attenuating testis toxicity induced by microwave radiation [18], 2-bromopropane [19], and busulfan [20]; thus, melatonin may be useful in preventing the effect of cisplatininduced toxicity on fertility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cisplatin is an effective anticancer drug, but it has demonstrated toxicity to the bladder [15], inner ear [16], peripheral nerves [17], and reproductive system [15]. Melatonin is capable of attenuating testis toxicity induced by microwave radiation [18], 2-bromopropane [19], and busulfan [20]; thus, melatonin may be useful in preventing the effect of cisplatininduced toxicity on fertility.…”
Section: Discussionmentioning
confidence: 99%
“…1a). Then, a working concentration of 250 µM cisplatin was selected, on the basis of a previous report [15], for use in combination with human sperm and different concentrations of melatonin. Our experimental results showed that only 100 mM melatonin could restore cisplatin-induced sperm dysfunction, and 5, 12.5, and 50 mM melatonin could not recover either total motility or progressive motility (Fig.…”
Section: Melatonin Significantly Restored Human Sperm Motilitymentioning
confidence: 99%
“… [ 66 ] Cisplatin-Induced Bladder Cystopathy Female SD rats 6 mg/kg, 5 consecutive days RBSMCs, SV-HUC-1, ATCC, Manassas, VA NGF, HO-1 CUR via targeting NRF2 could ameliorate cisplatin-induced cystopathy. [ 67 ] Pain Male Swiss mice 3, 10, 30 mg/kg, subcutaneously, 1 h before stimulation - NF-ĸB, HO-1, TNF-α, IL-10, IL-1β CUR via reducing NF-κB activation and increasing Nrf2 expression could inhibit superoxide anion-induced inflammatory pain-like behaviors. [ 68 ] Endotoxemia Male Wistar rats 25,50, and 100 mg/kg, orally, 2 consecutive days - TNF-α, IL1-β CUR via modulating the activity of Nrf2 could prevent LPS-induced sickness behavior and fever possibly.…”
Section: Other Conditionsmentioning
confidence: 99%
“…Curcumin’s antioxidative effects on bladder function are dependent on the promotion of the Nrf2 HO-1 pathway. It limited apoptotic enzymes, supported NGF protein synthesis and applied neurorestorative impacts on the urinary bladder in cisplatin-induced bladder injury in rats [ 94 ].…”
Section: Nrf2 Is An Essential Factor For Curcumin Effects On the Cellular Processes And Enzymesmentioning
confidence: 99%